EFFECT OF PASTURE ENCLOSURE AND DUNG DROPPINGS ON SOIL NUTRIENTS AND ABOVEGROUND BIOMASS IN ALPINE GRASSLAND IN THE NORTHERN TIBETAN PLATEAU - Zengrang Xu; Chunxia Lu; Shengkui Cheng; G. C. Dhruba Bijaya (Journal of Animal and Plant Sciences, 2016)
Pasture enclosure to prevent from grazing and dung droppings are the two widely-used options for degraded grasslands to restoration. The effects of pasture enclosure and dung droppings on soil nutrients and aboveground biomass were evaluated in plot scale in alpine meadow in the northern Tibetan plateau in this study. A plot with 10 m ×15 m was set up in July 2012. We have conducted three treatments: dung droppings within enclosures (DF), enclosures only (F), and open grazing (CK). Samples of soil and aboveground biomass were collected in subplots during the growing seasons of 2013 and 2014. The lab analysis and statistical analysis are also applied. Both pasture enclosures and dung droppings were found to improve soil nutrients and enhance aboveground net primary production in different degree. However, pasture enclosure remained effective through the second year after their construction, while the fertilization benefits of dung droppings were lasting no more than a year. It’s suggested that: 1) pasture enclosure should be properly used to recover the degraded grassland, especially the rational duration of pasture enclosure should be explored further in the alpine grassland; 2) increase the proportion of dung droppings on grassland with advocating the growth of renewable energy, thereby promote nutrient cycling, improve soil conditions, and enhancing net primary production.
Keywords: pasture enclosure; dung droppings; alpine meadow; soil nutrients; aboveground net primary productivity